Preparing Health Services for Climate Change in Australia - Blashki, G.; Armstrong, G.; Berry, H.; Weaver, H.; Hanna, E.; Bi, P.; Harley, D.; Spickett, Jeffery (Sage Publications, Inc., 2011)
Although the implications of climate change for public health continue to be elucidated, we still require much work to guide the development of a comprehensive strategy to underpin the adaptation of the health system. Adaptation will be an evolving process as impacts emerge. The authors aim is to focus on the responses of the Australian health system to health risks from climate change, and in particular how best to prepare health services for predicted health risks from heat waves, bushfires, infectious diseases, diminished air quality, and the mental health impacts of climate change. In addition, the authors aim to provide some general principles for health system adaptation to climate change that may be applicable beyond the Australian setting. They present some guiding principles for preparing health systems and also overview some specific preparatory activities in relation to personnel, infrastructure, and coordination. Increases in extreme weather–related events superimposed on health effects arising from a gradually changing climate will place additional burdens on the health system and challenge existing capacity. Key characteristics of a climate change–prepared health system are that it should be flexible, strategically allocated, and robust. Long-term planning will also require close collaboration with the nonhealth sectors as part of a nationwide adaptive response.